Immuno-protective impact of Kangfuxin liquid on systematic toxicity associated with autologous hematopoietic stem cell transplantation in multiple myeloma - Wu, Xianyi; Tang, Mingxuan; Deng, Taohua; Qu, Fujun; Jiang, Fang; Zhou, Qin; Lin, Wenyuan; Wang, Xiaotao (Frontiers in Medicine, 2025)
ObjectiveThis study evaluated the effectiveness of Kangfuxin liquid against autologous stem cell transplantation toxicity in patients with multiple myeloma.MethodsThis single-center retrospective study involved 82 participants, divided into the simple oral cryotherapy group (control group), which included 43 patients with multiple myeloma who underwent autologous hematopoietic stem cell transplantation before May 2023, and the Kangfuxin liquid + oral cryotherapy group (experimental group), which included 39 patients with multiple myeloma, who underwent autologous hematopoietic stem cell transplantation after June 2023. Statistical analysis indicators included infection, gastrointestinal toxic side effects, efficacy evaluation, and prognostic analysis.ResultsCompared with the control group, the experimental group had a higher mean age (p = 0.003), fewer reinfused stem cells (p < 0.001), and a longer neutrophil and platelet engraftment time (p = 0.001 and p < 0.001). The experimental group had lower auxiliary treatment costs (p < 0.0001), and significantly lower infection incidence (p = 0.001) and mucositis and diarrhea grading (p = 0.046), indicating a protective effect. There were no additional adverse reactions, and the treatment efficacy for the patients’ primary diseases remained unaffected.ConclusionKangfuxin liquid significantly reduces mucosal damage, shortens hospitalization, lowers medical costs, and does not compromise the therapeutic efficacy of autologous transplantation for multiple myeloma, providing evidence for clinical treatment.